Pedagogical Directive Utterances in Indonesian Language Learning at Muhammadiyah Islamic Junior Secondary School 1, Malang City: A Sociopragmatic Study Supporting SDG 4 - Musaffak Musaffak; Kisyani Laksono; Mulyono Mulyono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To examine the forms, directness strategies, pedagogical functions, and sociopragmatic motivations of teachers' directive utterances in Indonesian language learning at Muhammadiyah Islamic Junior Secondary Schools1, Malang City. Method: A qualitative case-study design is proposed, combining non-participant observation, audio-video recording, field notes, and teaching-document analysis. Directive units are interpreted through an integrated coding matrix covering linguistic form, degree of directness, pragmatic modifiers, lesson phase, and pedagogical uptake. Descriptive frequencies are used only to display the qualitative patterning of the corpus. Results: The provisional analytical model indicates that commands and instructions constitute the largest category (31.18%), followed by question-directives (23.66%) and requests (16.13%). Direct strategies account for 55.91% of the modeled corpus, yet their interpersonal force is frequently softened by markers such as silakan, coba, mari, vocatives, and the particle ya. Procedural organization, participation elicitation, and cognitive scaffolding emerge as the dominant pedagogical functions. Novelty: Rather than treating directives as isolated sentence types, this study connects form, social relations, pedagogical purpose, and student uptake in a single sociopragmatic-pedagogical framework. The analysis demonstrates how teacher authority can be enacted without eliminating solidarity, dialogic participation, or value-sensitive communication in an Islamic junior secondary school.